2020
DOI: 10.1038/s41467-020-16923-0
|View full text |Cite
|
Sign up to set email alerts
|

Iron imaging in myocardial infarction reperfusion injury

Abstract: Restoration of coronary blood flow after a heart attack can cause reperfusion injury potentially leading to impaired cardiac function, adverse tissue remodeling and heart failure. Iron is an essential biometal that may have a pathologic role in this process. There is a clinical need for a precise noninvasive method to detect iron for risk stratification of patients and therapy evaluation. Here, we report that magnetic susceptibility imaging in a large animal model shows an infarct paramagnetic shift associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 61 publications
5
27
1
Order By: Relevance
“…As expected, hypointense regions had the highest R * 2 of all regions, which was consistent with intramyocardial hemorrhage and significantly higher iron content than other regions. 16,33 RE was found to be close to 7/3 (RE = 2.20) when analyzing R * 2 measurements at 7T versus 3T, showing that R * 2 scales with field strength as shown in previous work. 30,31 The relationship between R * 2 and magnetic susceptibility is similar to that reported in the human brain.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…As expected, hypointense regions had the highest R * 2 of all regions, which was consistent with intramyocardial hemorrhage and significantly higher iron content than other regions. 16,33 RE was found to be close to 7/3 (RE = 2.20) when analyzing R * 2 measurements at 7T versus 3T, showing that R * 2 scales with field strength as shown in previous work. 30,31 The relationship between R * 2 and magnetic susceptibility is similar to that reported in the human brain.…”
Section: Discussionsupporting
confidence: 83%
“…Relaxation time mapping and QSM was performed on whole-heart explants, and there may be differences from live animals and humans. The feasibility of implementing in vivo cardiac QSM was recently shown in healthy patients, 45 a swine model of MI reperfusion injury, 16 and ST-elevation MI patients. 16 These studies were conducted at 3T or 1.5 T. Based on the findings in this study, we would expect to see differences in vivo at 7T.…”
Section: Limitationsmentioning
confidence: 99%
“…To investigate UNIC's ability to improve pathological MRI contrast, canine models with and without hemorrhagic myocardial infarction (hMI) were studied to investigate whether UNIC shimming can improve visualization of focal myocardial iron deposition. Focal iron deposition in the heart caused by hMI can lead to life-threatening adverse events [50][51][52][53][54] . Recent studies have shown that reliable detection of iron deposition post-myocardial infarction can play a crucial role in risk stratification and treatment evaluation 50,51,53 .…”
Section: Unic Reveals Pathological Lesions In the Heart That Were Masked By B0 Inhomogeneity Artifacts Under The State-of-the-art Scannermentioning
confidence: 99%
“…Focal iron deposition in the heart caused by hMI can lead to life-threatening adverse events [50][51][52][53][54] . Recent studies have shown that reliable detection of iron deposition post-myocardial infarction can play a crucial role in risk stratification and treatment evaluation 50,51,53 . The ferromagnetic nature of iron has made T2* MRI the desirable noninvasive method to image myocardial iron deposition.…”
Section: Unic Reveals Pathological Lesions In the Heart That Were Masked By B0 Inhomogeneity Artifacts Under The State-of-the-art Scannermentioning
confidence: 99%
“…Currently, reperfusion injury is considered the major complication of vascular reperfusion therapy for acute myocardial infarction (MI) and is estimated to occur in up to 60% of patients (Moon et al. 2020 ). Inhibition of reperfusion injury is key to the treatment of MI.…”
Section: Introductionmentioning
confidence: 99%